Prevalence of Salmonella Isolated from Retail Meats in Mueang District, Nakhon Si Thammarat Province - เลี่ยมทอง, สุมาลี (Wichcha Journal Nakhon Si Thammarat Rajabhat University, 2017)
Salmonella is one of the most important food borne pathogens. This bacterium is a major public health concern throughout the world. Salmonellosis is mainly caused by consumption of contaminated meat. The objective of this study was to investigate the prevalence of Salmonella in retail meats at wet markets and supermarkets in Mueang district, Nakhon Si Thammarat province from May to October 2016. From a total of 172 retail meat samples, 116 samples were positive for Salmonella (67.4%) with 74.6% from wet market (67/90) and 59.8% (49/82) from supermarkets. The prevalence of Salmonella in each type of meat was higher than 50%. Detection of this bacterium in pork, chicken and beef were 75.0% (45/60), 73.3% (45/60) and 51.9% (27/52), respectively. The data presented in this study demonstrates that most of retail meats in Mueang district, Nakhon Si Thammarat are contaminated with Salmonella. Therefore, decrease this bacterium contamination in retail meats should be implemented to reduce the risk of human infections.